An aquaglyceroporin governs cellular water and CO 2 conductance relevant for vesicular mineral formation in a marine calcifier - Ann-Sophie Matt; Smilla Tetzlaff; Sima Jonusaite; Alex Quijada-Rodriguez; Marcus Schewe; Sönke Cordeiro; Dirk Weihrauch; Marian Y. Hu (Proceedings of the National Academy of Sciences, 2026)
Many marine organisms generate biominerals by endocytotic uptake of seawater which is modified within calcifying cells to produce an amorphous mineral precursor required to form the mineralized shell or skeleton. In this process, water must be removed from the endocytotic vesicles and the cell to promote concentration of calcification substrates and production of a water-free mineral. Here, we demonstrate that in the sea urchin larva, an aquaglyceroporin (spAQP9) is involved in the cellular calcification process. spAQP9 is found exclusively in the calcifying primary mesenchyme cells (PMCs), and spAQP9 expression is increased during mineralization underlining its role in skeleton formation. Heterologous expression of sp AQP9 in Xenopus laevis oocytes demonstrated that this channel conducts water and carbon dioxide. The water conductance by spAQP9 is sensitive to phloretin with an IC 50 of ∼38 µM and treatment of larvae with phloretin or knock-down of spAQP9 impaired skeleton formation. Immunohistological analyses revealed localization of spAQP9 in vesicles with different subcellular distribution depending on the calcification activity of PMCs. Finally, we developed an in vivo assay to measure cellular and vesicular water permeability in PMCs and found a significant water permeability of the plasma membrane and membranes of calcium-rich vesicles. The results of this work highlight the importance of water transport mechanisms in the mineralization process. Here, aquaporins like spAQP9 represent key players that serve a dual function as a water and CO 2 conductance pathway and thereby can support ion concentration and carbon transport, two processes that are of fundamental importance to promote intracellular mineral precursor formation.